ANALYSIS OF PLANNING, IMPLEMENTATION, ASSESSMENT OF LEARNING FROM HOME STRATEGIES DURING THE COVID-19 PANDEMIC IN PRIVATE ELEMENTARY SCHOOLS - Beti Istanti Suwandayani; Dyah Worowirastri Ekowati; Sony Darmawan; Ari Dwi Haryono (Al-Bidayah : jurnal pendidikan dasar Islam, 2021)
The impact of the COVID-19 virus is so significant. Efforts have been taken to handle the impacts on various fields, including in-field education. The Indonesian government has established three policies in education, one of which is learning from home. This article analyzes the planning, implementation, assessment of learning from home strategies during the COVID-19 pandemic in private elementary schools. The research was conducted qualitatively, and the type of research was descriptive. The instruments of this research were interviews, indirect observations, and documentation studies. The research subjects were two principals, two teachers, two students, two guardians of students from each elementary school, i.e., Muhammadiyah 9 Elementary School and Bani Hasyim Islamic Elementary school, both in Malang, East Java, Indonesia. Among the research subjects, the Principal of each school is the key informant in this study. The results of the analysis show that the lesson planning already includes the use of lesson plans. However, communication with students and parents is done through PANDAWA applications and daily learning scenarios, which contain materials, teaching materials, LKPD, and assessment questions. The implementation of learning is carried out synchronously and asynchronously. The learning assessment is conducted by sending questions using various applications such as Edmodo, Quilgo, Google Classroom, and the PANDAWA website. Various forms of innovation in learning services while learning from home are key parts in improving the quality of private elementary schools.